Vibrio vulnificus mutation rate: an in vitro approach - Roig Molina, Francisco Jose; Amaro González, Carmen; Alcaine Otín, Alejandro; Carro Fernández, Jesús (Frontiers in Microbiology, 2023)
Vibrio vulnificus is a multi-host pathogenic species currently subdivided into five phylogenetic lineages (L) plus one pathovar with the ability to infect fish due to a transmissible virulence plasmid (Roig et al., 2018). This plasmid (or a fragment of it) has been transmitted between lineages within the species, contributing to the evolution of V. vulnificus. The aim of the study was to provide an experimental approximation to the V. vulnificus mutation rate through determining spontaneous mutation rates from bacterial cultures of representants of the different lineages by whole-genome sequencing. To this purpose synonymous SNP differences, spontaneous mutation not subjected to the evolutive forces, between initial and final culture after serial growth were evaluated and used for mutation rate calculation